Tectonic and geothermal controls on dolomitization and dolomitizing fluid flows in the Cambrian-Lower Ordovician carbonate successions in the western and central Tarim Basin, NW China - Ngia, Ngong Roger; Hu, Mingyi; Gao, Da (Journal of Asian earth sciences, 2019)
[Display omitted] •Dolomitizing fluids were brine-rich connate seawaters and hydrothermal fluids.•Tectonic compression, thermal convective circulation influenced fluid flow.•Penecontemporaneous supratidal, burial and hydrothermal dolomitization are proposed.•Intercrystalline pores and vugs are the main types of porosity in the dolomites.•Carbonate environments were restricted-evaporative lagoonal and open platform. The deeply buried Cambrian-Lower Ordovician carbonates in the western and central Tarim Basin were extensively dolomitized in the course of their diagenetic history. Petrographic, geochemical (O-C-Sr-isotopes and trace elements) and fluid inclusion studies have been used in this study to elucidate the origins of the ancient massive dolomites. Based on detailed examination, dolomicrite and microbial (or algal)-laminated dolomites (DML) and three types of crystalline dolomites (fine-crystalline, nonplanar-a(s), dolomite (RD1), fine- to medium-crystalline, planar-e (s) dolomite (RD2), and medium- to coarse-crystalline, nonplanar-a dolomite (RD3)) are identified. Nonplanar-a dolomite (saddle) cement (CD), and early and later-stage calcite cement as vug/fracture infills are identified. Most samples of DML still possess relics of algal stromatolitic and anhydritc sediment fabrics, common in Sabkha dolomites formed during penecontemporaneous supratidal dolomitization. The occurrence of RD1 and RD2 along low-amplitude stylolites in most samples indicates that their formation was somewhat linked with pressure dissolution by which minor Mg ions were probably released for replacive dolomitization during early shallow-burial dolomitization. Moreover, the curved crystal faces and the tightly packed crystals of RD2 and RD3 with irregular overgrowth rims and increasing crystal sizes may have resulted from the recrystallization and replacement upon the RD1 and/or from the cortical overgrowth and dissolution of remaining precursor limestones by the influx of dolomitizing fluids during late shallow-burial dolomitization. The average range of the homogenization temperatures (Th) of CD dolomites is 87.1 °C to 161.5 °C, mostly lower than the estimated ambient temperature (60 °C to 240 °C) for the Cambrian-Lower Ordovician strata, implying that the growth of the CD dolomites in the study area was of ‘geothermal’ origin during late shallow to deep-burial dolomitization. The large overlap of δ18O, δ13C and 87Sr/86Sr values of RD2, RD3 and CD dolomite suggest that the dolomitizing fluids that precipitated the dolomite cement apparently inherited the composition of the remnant saline connate seawater preserved in host limestones/dolomites and siliciclastics in the Terreneuvian to Cambrian Series 3 strata through fluid–rock interaction. The conceptual model to explain tectonic influence on dolomitizing fluid flows show that faults, fractures and permeable horizons which evolved from a strong tensional-compressional tectonic during the Late Hercynian orogeny in this basin effectively provided conduits through which extensive cross-formational and ascending higher-temperature saline-rich dolomitizing fluids were driven by thermal convective-advective circulation due to geothermal variation, forming irregular networks of dolomites, CD dolomite and calcite cements in the host carbonate rocks.